Spatial Transitions: Cape Town Case Study - Isaacs, Fadly (Science, 2016)
The research is guided by the following question: What are the spatial dimensions of social justice when thinking about Cape Town as a post-apartheid city? In principle the research intends, by advancing a diachronic approach to the examination of spatial form, to critically analyse the spatial (physical) structure of the city at a range of scales and relate these to both the higher level normative /cultural imperatives as well as the associated functional organisational aspects that have been institutionalised at different moments in the history of Cape Town.